Establishing a causal role for left ventrolateral prefrontal cortex in value-directed memory encoding with high-definition transcranial direct current stimulation. (12th March 2023) - Han, Linfeng Tony; Cohen, Michael S.; He, Liqin Ken; Green, Laura M.; Knowlton, Barbara J.; Castel, Alan D.; Rissman, Jesse
Abstract: One critical approach for promoting the efficiency of memory is to adopt selective encoding strategies to prioritize more valuable information. Past neuroimaging studies have shown that value-directed modulation of verbal memory depends heavily on the engagement of left-lateralized semantic processing regions, particularly in the ventrolateral prefrontal cortex (VLPFC). In the present study, we used high-definition transcranial direct current stimulation (HD-tDCS) to seek evidence for a causal role of left VLPFC in supporting the memory advantage for high-value items. Three groups of healthy young adult participants were presented with lists of words to remember, with each word accompanied by an arbitrarily assigned point value. During the first session, all participants received sham stimulation as they encoded five lists of 30 words each. Two of these lists were immediately tested with free recall, with feedback given to allow participants to develop metacognitive insight and strategies to maximize their point total. The second session had the exact same structure as the first, but the groups differed in whether they received continued sham stimulation ( N  = 22) or anodal stimulation of the left VLPFC ( N  = 21) or right VLPFC ( N  = 20). Those lists not tested with immediate recall were tested with recognition judgments after a one-day delay. Since no brain stimulation was applied during this Day 2 test, any performance differences can be attributed to the effects of stimulation on Day 1 encoding processes. Anodal stimulation of left VLPFC significantly boosted participants' memory encoding selectivity. In comparison, no such effect was seen in participants who received right VLPFC or sham stimulation. Estimates of recollection- and familiarity-based responding revealed that left VLPFC stimulation specifically amplified the effects of item value on recollection. These results demonstrate a causal role for left VLPFC in the implementation of selective value-directed encoding strategies, putatively by boosting deep semantic processing of high-value words. Our findings also provide further evidence on the hemispheric lateralization of value-directed verbal memory encoding.